The Development Of Attention, Relevance, Confidence, And Satisfaction (ARCS) Model Based on Active Learning to Improve Students'learning Motivation - Pratama, Riska Widya; Sudiyanto, Sudiyanto; Riyadi, Riyadi (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This research and development aim to: (1) develop a valid and practical model so that it can improve students' motivation in learning mathematics, (2) know the effectiveness of the active learning based ARCS model. This research refers to the stages of research and development from Borg and Gall which has been modified by Sukmadinata into 3 stages, namely preliminary studies, product development, and product testing. Data analysis techniques used are descriptive qualitative and quantitative. The research finds that (1) active learning based on ARCS model is valid and practical to improve students' learning motivation in mathematics learning based on the assessment given by education experts of 77.94% (good category), material experts of 87.14% (excellent category), and practitioners of 96.56% (excellent category). (2) The result of the effectiveness test shows that the developed product is effective in increasing students' learning motivation in mathematics learning based on experimental results which shows p less than 0.05 on learning motivation which means there are significant differences in students who were taught using the ARCS model based on active learning.